FRI0207 Real-World Comparative Risks of Herpes Virus Infections in Tofacitinib and Biologic-Treated Rheumatoid Arthritis Patients. (15th July 2016) - Curtis, J.R.; Xie, F.; Yun, H.; Bernatsky, S.; Winthrop, K.L.
Abstract : Background: While placebo-controlled clinical trials have suggested an increased rate of herpes zoster (shingles) with tofacitinib, the real-world risks of herpes zoster and herpes simplex associated with tofacitinib compared to other biologics for rheumatoid arthritis are largely unknown. Objectives: To evaluate the risks of herpes zoster (HZ) and herpes simplex virus infection (HSV) associated with tofacitinib compared to biologic agents among patients with rheumatoid arthritis (RA). Methods: Using health plan data, we identified RA patients without a history of HZ or HSV who initiated tofacitinib or biologics from 2010–2013. Among this cohort, new cases of HZ or HSV were found and incidence rates calculatedby drug. We used Cox proportional hazards models evaluated the adjusted association between tofacitinib and either HZ, and a composite outcome of HZ or HSV. Results: A total of N=1, 746 patients initiating tofacitinib were compared with initiations of other biologics including anti-TNF (n=38, 871), abatacept (n=11, 434), rituximab (n=4, 785), and tocilizumab (n=6, 266). Tofacitinib patients were somewhat younger (mean age 57 years) versus those on other biologics, and somewhat less likely to use concomitant MTX (39% vs. 44–56%, depending on drug). Crude incidence of HZ associated with tofacitinib was 4.33/100py and after multivariable adjustment, was significantly elevated (hazard ratio, HR=2.09, 95% CI 1.33–3.26) compared to abatacept (referent). Rates and adjusted HRs for all other RA biologics were comparable to each other and abatacept. Older age, female sex, prednisone >7.5mg/day, prior outpatient infection, and greater number of hospitalizations were also associated with increased HZ risk Incidence rates for the combined outcome were greatest for tofacitinib (9.33/100py) and also significantly elevated after adjustment (HR=1.65, 95%CI 1.21–2.23). Conclusions: Zoster infections were relatively common among RA patients. The risk for zoster associated with tofacitinib was approximately double that observed in patients using biologics. Acknowledgement: This project had no external funding Disclosure of Interest: J. Curtis Grant/research support from: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, AbbVie, Consultant for: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, AbbVie, F. Xie: None declared, H. Yun Grant/research support from: Amgen, S. Bernatsky Grant/research support from: Supported by the Drug Safety and Effectiveness Network, Canadian Institutes of Health Research, K. Winthrop Grant/research support from: Unrelated work with Pfizer, UCB, Genentech, AbbVie, Lilly, BMS, Consultant for: unrelated work with Pfizer, UCB, Genentech, AbbVie, Lilly, BMS